If it's not what You are looking for type in the equation solver your own equation and let us solve it.
t in (-oo:+oo)
2-((1/3)*t) = 0
(-1/3)*t+2 = 0
2-1/3*t = 0 // - 2
-1/3*t = -2 // : -1/3
t = -2/(-1/3)
t = 6
t = 6
| 6+z(9)=9 | | -4(-3x-8)-4x+8= | | 15/30=6/x | | -100=n+8 | | -100=n+8 | | -100=n+8 | | -100=n+8 | | 15/30=6/x | | -100=n+8 | | -100=n+8 | | -100=n+8 | | -100=n+8 | | -8x+3+3x=13 | | 7x=3(3x-4) | | 7x+5(4-2x)=5 | | (x-35)+90+43=180 | | (8x+4)(8x-4)=y | | -6x+7(2x+6)=142 | | -90-6x=48-12x | | -100=n+8 | | 7x+5(4-2x)=5 | | (8x+4)(8x-4)=y | | -4(-3x-8)-4x+8= | | (x-35)+90+43=180 | | 6(p+8)= | | -90-6x=48-12x | | -4(-3x-8)-4x+8= | | 6(p+8)= | | x+28500-y=371500 | | 6(p+8)= | | x+28500-y=371500 | | 15/30=6/x |